Memory impairment is not necessarily related to seizure frequency in mesial temporal lobe epilepsy with hippocampal sclerosis - Pacagnella, Denise (2014)
Objective: To investigate the effect of seizure frequency on memory, we performed a cross sectional study comparing mesial temporal lobe epilepsy (MTLE) patients with frequent and infrequent seizures.Methods: We performed magnetic resonance imaging (MRI) hippocampal volume (HV) measurements and neuropsychological assessment in 22 patients with frequent seizures (at least one dyscognitive seizure [DS] per month) that were refractory to antiepileptic drugs and 20 patients with infrequent seizures (three or less DS per year and no event evolving to a bilateral convulsive seizure), all with MRI signs of hippocampal sclerosis (HS) on visual analysis. We also included 29 controls for comparison of volumetric data.Results: There was no difference in memory performance between patients with frequent seizures and infrequent seizures. We observed a significant bilateral reduction of HV in patients with MTLE when compared to controls (p < 0.001). the degree of hippocampal atrophy (HA) between patients with frequent and infrequent seizures was not different. There was a negative correlation between seizure frequency and HV, with r = -0.3 for the HV ipsilateral to the HS and r = -0.55 for the contralateral side, thus, explaining only 9% and 30% of the HV loss. There was a positive correlation between age of onset and degree of HA (r = 0.37).Significance: Our data suggest that seizure frequency does not explain most of the HV loss or memory impairment in MTLE. Memory impairment appears to be more influenced by hippocampal damage than by seizure frequency. Further studies are necessary to identify the factors that influence memory decline in patients with MTLE.